The Place of the Representative Dictionary in Regional Lexicography. Theory and Practice - Ahumada, Ignacio (2024)
The so-called representative regional dictionary is framed within the increasingly extensive typology of regional dictionaries of Spanish (differential and integral, fundamentally). It is a repertoire model that registers not only the lexicon that differs from the standard, but also those words of the general language that represent for the speakers part of their linguistic and cultural identity due to their fully identification with their geolectal variety. The proposal includes, in part, lexical selection criteria found in the traditional dictionaries of regionalisms (zoonyms and phytonyms) or lexicalizations determined by the social acceptance of certain phonetic phenomena, etc. and, in terms of microstructure, the organization of the lexicographic article into three perfectly differentiated blocks: linguistic information, multidisciplinary gloss, and onomasiological reference.